Physicochemical properties of silver catfish (Pangasius sutchi) skin gelatin produced as affected by different extraction time / Normah, I., Nur Ain, H. and Effaniza, E.H - I., Normah; H., Nur Ain; E.H., Effaniza (Universiti Teknologi MARA, Perlis, 2014)
Gelatin was extracted from silver catfish (Pangasius sutchi) skin and the effects of extraction time on the physicochemical characteristics of the gelatin were studied in comparison with commercial bovine gelatin. The skin was initially pre-treated by washing in 0.19N NaOH and 0.12N acetic acid prior to gelatin extraction at 50°C for 6, 8, 10 and 12 hrs. The extracts were filtered, freeze dried and then ground. Yield was recorded and the gelatin was analysed for viscosity, molecular weight distribution, amino acids composition, gel strength, melting point, setting point and setting time. Longer extraction time resulted in higher gel strength and melting point while the gel sets at lower temperature and requires shorter setting time than commercial bovine gelatin. The yields were 10.40% and 11.42% at 10 and 12 hrs extraction time, respectively. Extracted gelatins showed higher gel strength and contain higher amount of proline, lysine, phenylalanine and glycine than the commercial bovine gelatin. High molecular weight bands between 80 to 175 kDa were observed in all the extracted gelatins. Therefore, in this study, 10 hrs extraction time is considered as the optimum duration for silver catfish gelatin production as it produces gelatin with high gel strength and viscosity values as well as acceptable yield. In view of its high gel strength and viscosity value, silver catfish skin gelatin has the potential to be used as gelling agent in food.